Trends in lung cancer incidence in Sri Lanka from 2005-2019 - Muzrif Munas; Mekala Fernando; Sachintha Dilhani; Sashiprabha Nawaratne (College of Community Physicians of Sri Lanka, 2022)
Introduction: Studies carried out on the incidence of lung cancer in the world and Southeast Asia region have shown varying trends. This is the first study in Sri Lanka after 2010 on trends of lung cancer.   Objectives: To describe the trends in lung cancer incidence and patterns in Sri Lanka.   Methods: All newly diagnosed 'trachea bronchus and lung' cancer patients in Sri Lanka during 2005-2019 included in the National Cancer Registry, Sri Lanka (NCR-SL) were analysed. Crude incidence rates (CR) and age standardized incidence rates (ASR) were compared using the Joinpoint regression program.   Results: Data of 19 815 trachea bronchus and lung cancer patients (males=15292; 77.17%) were analysed. The joinpoint regression analysis observed a linear increasing trend of CR and ASR of lung cancer from 2005-2019. The proportional increase was higher for females (average annual percentage change (AAPC) of CR=8.5 and ASR=6.16) than males (AAPC of CR=5 .4 and ASR =3 .48) and the increase was statistically significant for both sexes.   Conclusions & Recommendations: In Sri Lanka, the incidence of lung cancer has shown an increasing trend with a greater proportional rise in females. Although the increase could be partially explained by indoor air pollution, the rise could be due to other unknown factors, which warrants detailed studies on lung cancer in Sri Lanka.